2016
DOI: 10.1111/aas.12692
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a communication strategy on family satisfaction in the intensive care unit

Abstract: No significant improvement in family satisfaction of critically ill adult patients could be found after implementing the VALUE strategy. Whether these results are due to insufficient training of the new strategy or a missing effect of the strategy in our socio-economic environment remains to be shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Madsen et al 5 also cite a study of Dubois et al 8 as providing data supporting their position. It should be noted that the authors also reported that 40% of the patients in the deep block group still had incidents with inadequate surgical conditions The lesson that we take away from this latter observation is that deep neuromuscular block is not a cure-all.…”
Section: Definitions a Fundamental Disagreementmentioning
confidence: 90%
See 2 more Smart Citations
“…Madsen et al 5 also cite a study of Dubois et al 8 as providing data supporting their position. It should be noted that the authors also reported that 40% of the patients in the deep block group still had incidents with inadequate surgical conditions The lesson that we take away from this latter observation is that deep neuromuscular block is not a cure-all.…”
Section: Definitions a Fundamental Disagreementmentioning
confidence: 90%
“…It should be noted that the authors also reported that 40% of the patients in the deep block group still had incidents with inadequate surgical conditions The lesson that we take away from this latter observation is that deep neuromuscular block is not a cure-all. Madsen et al 5 also cite a study of Dubois et al 8 as providing data supporting their position. We discuss the limitations of this study in greater detail in our earlier review 9 but briefly, in the shallow or moderate block group of the Dubois study, the initial dose of rocuronium was only 0.45 mg/kg and the average duration of surgery in this group was 74 AE 23 min.…”
Section: Definitions a Fundamental Disagreementmentioning
confidence: 90%
See 1 more Smart Citation
“…The FS-ICU has been translated into several languages, including Swiss Italian. In this study, we used the Swiss Italian version (Pagnamenta et al, 2016) after making minor changes to the wording of items to tailor the questionnaire to the Italian setting. Translation and back-translation method was used to ensure the fidelity of the Italian translation.…”
Section: Methodsmentioning
confidence: 99%
“…While responsiveness remains a major domain of health system performance [ 32 ], the use of complaints to enhance the responsiveness might provide timely action for quality improvement. Despite difficulties remaining in the implementation of strategies to improve family satisfaction [ 33 ], we believe the analysis of healthcare complaints, including those to the ICUs, is of high value in quality improvement.…”
Section: Discussionmentioning
confidence: 99%